Introduction to English Vocabulary Through the Implementation of the Singing Based Method for Children at Saint Don Bosco Catholic Kindergarten Mataram - Hastuti, Hilda; Lela Rahmawati; Diah Supatmiwati; Nur Alfilail; Agus Syahid; Zainuddin Abdussamad (Society : Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aims to introduce English vocabulary to kindergarten students by using songs and singing as an enjoyable learning method. This activity was initiated to foster an interactive and enjoyable learning atmosphere for early childhood learners. Singing was selected as the instructional method because songs can increase young EFL learners’ motivation and encourage their active participation in English learning. The singing-based method was implemented through nine stages, namely: (1) identification of the learning theme, (2) song planning, (3) preparation of learning media, (4) opening activity, (5) vocabulary introduction, (6) main singing-based activity, (7) vocabulary reinforcement, (8) simple evaluation, and (9) closing activity. The vocabulary introduction activity employed a singing-based approach using modified lyrics adapted from the song My Finger Family. The lyrics were modified to the learning theme, My Needs, and accompanied by simple gestures to facilitate natural vocabulary acquisition among young learners. The findings of this activity indicated improvements in children’s ability to retain new vocabulary, increased enthusiasm for learning, and higher levels of active participation in group singing activities. The results further suggest that the implementation of the singing-based method is effective in sustaining children's attention and fostering a positive and engaging learning atmosphere. Overall, the activity confirmed that the singing-based method is an effective, engaging, and age-appropriate instructional approach for enhancing children's acquisition of basic English vocabulary. The program is recommended for sustained integration into daily classroom activities in kindergarten settings to support children's English vocabulary development.